Investigation on the effect of Polyethylene Terephthalate (PET) fiber and crumb rubber on energy absorption capacity of concrete - Mahmoud, Fatima; Noaman, Ahmed (Iraqi Journal of Civil Engineering, 2024)
The accumulation of wastes, especially plastic and car tires, has become a major problem facing society today. Therefore, through this research, these wastes were recycled and used to improve some properties of concrete. Recycled crumb rubber from car tires was used instead of sand as a partial replacement of 10%. The substitution was done by two methods: random and equivalent size substitution. As well, 1%polyethylene terephthalate (PET) fiber was added by the volume of concrete to improve some properties of rubberized concrete. Compressive strength, ultrasonic pulse velocity test (UPV) were conducted in this study to investigate the efficiency of PET rubberized concrete, as well the impact resistance test was also conducted to investigated the ability of PET rubberized concrete in term of energy absorption. Slabs of size (50cm×50cm×5cm) were utilized for low velocity impact test. The results indicated there were a reduction in compressive strength and UPV results were observed in PET fiber rubberized concrete the reduction were (37.47% and 5.4%) respectively as compared with PETC mixture and the result of dynamic modulus of elasticity show the same pattern of UPV result , in contrast there was an improvement in the impact resistance when PET fiber and crumb rubber were used it increased by(117.63% and 52.9% ) for random and equivalent replacement respectively as compared with PETC.